2013
DOI: 10.15430/jcp.2013.18.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA Damage Response in Helicobacter pylori-Infected Mongolian Gerbils

Abstract: Helicobacter pylori (H. pylori) induced DNA damage which may be related to gastric cancer development. The DNA damage response coordinates DNA repair, cell-cycle transition, and apoptosis through activation of DNA damage response molecules. The damaged DNA is repaired through non-homologous end joining (NHEJ) or homologous recombination (HR). In the present study, we investigated the changes of HR DNA repair proteins (ataxia-telangiectasia-mutated; ATM, ATM and Rad3-related; ATR), NHEJ repair proteins (Ku70/80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
4
2
Order By: Relevance
“…Their ndings showed increased expression of the TP53 and CHEK2 genes simultaneously, indicating that the cell is headed for cell death after the cell cycle arrest due to DSB (32). Moreover, ATM gene expression has decreased in most studies on cancerous tissues (33,34), which contrasts with the present study's ndings.…”
Section: Discussioncontrasting
confidence: 98%
“…Their ndings showed increased expression of the TP53 and CHEK2 genes simultaneously, indicating that the cell is headed for cell death after the cell cycle arrest due to DSB (32). Moreover, ATM gene expression has decreased in most studies on cancerous tissues (33,34), which contrasts with the present study's ndings.…”
Section: Discussioncontrasting
confidence: 98%
“…Ku protein levels are increased in H. pylori-infected gastric mucosal tissues of Mongolian gerbils (Bae et al 2013), suggesting that H. pylori enhances NHEJ pathways. In addition, Lim et al showed that H. pylori mediated activation NF-B-Cox2 axis helps to increase the expression of KU70/80 in human gastric cancer cells (Lim et al 2002).…”
Section: Helicobacter Pylori Triggers Dsb Repair Pathwaysmentioning
confidence: 99%
“…Gerbils are often used in the study of both bacterial infections (73, 74) and parasitic infections (75, 76). Gerbils are readily infected by both assemblage A (WBC6) and assemblage B (GS) strains, though infection clearance is delayed with GS (40).…”
Section: Discussionmentioning
confidence: 99%
“…The Mongolian gerbil or jird ( Meriones unguiculatus ) is a less commonly used, yet promising animal model for giardiasis ( 72 ). Gerbils are often used in the study of both bacterial infections ( 73 , 74 ) and parasitic infections ( 75 , 76 ). Gerbils are readily infected by both assemblage A (WBC6) and assemblage B (GS) strains, though infection clearance is delayed with GS ( 40 ).…”
Section: Discussionmentioning
confidence: 99%